Rousseau in Drag - Kennedy, R. author. aut Link
XIII, 186 p.
Keywords: Through a series of close readings of most of Rousseau's major writings, this book provides a new interpretation of the eighteenth-century philosopher's sexual politics. The text argues that Rousseau's writings provide a critique of not only normative gender identity, but also normative familial and kinship relations.